The Influence of the Smart Glucose Manager Mobile Application on Diabetes Management. (January 2019) - Gunawardena, Kasun C.; Jackson, Renee; Robinett, Iva; Dhaniska, Lahiru; Jayamanne, Shaluka; Kalpani, Sumedha; Muthukuda, Dimuthu
Background: Smartphone use is rapidly growing in developing countries, providing opportunity for development of new health-based mobile applications. The present study investigated the efficacy of a newly designed mobile application, Smart Glucose Manager (SGM), in Sri Lankan patients with diabetes. Methods: A total of 67 patients with access to Android smartphones were randomized into an SGM (n = 27) and a control group (n = 25). Glycosylated hemoglobin (A1c) levels were measured at baseline and every 3 months afterward. The SGM group utilized the application daily, while control-group patients were instructed to continue their standard methods of diabetes management. Independent t -tests were utilized to assess A1c differences at 3 and 6 months postrandomization. A1c improvement, defined as A1c at 6 months minus baseline, was compared with SGM usage to assess effectiveness of diabetic management. Results: At the 6-month follow up, the SGM group had significant lower A1c levels than the control group (7.2% vs 8.17%, P < .0001). For both groups, A1c values decreased from baseline to the 3 months (SGM: 9.52% to 8.16%, P < .0001; control: 9.44% to 8.31%, P < .0001). From 3 months to 6 months, the SGM group showed further improvement of A1c (−0.96% P < .0001), whereas the control group did not ( P = 0.19). A1c improvement was positively correlated with SGM usage ( R = .81, P < .001). Conclusion: The SGM, a mobile application specifically designed to support self-management of diabetes, appeared to show long-term improvement of A1c levels in patients with diabetes residing in Sri Lanka.